2023
DOI: 10.1177/14574969231178650
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy versus antibiotic therapy for acute cholecystitis in patients over 75 years: Randomized clinical trial and retrospective cohort study

Abstract: Background and objective: The prevalence of acute cholecystitis among elderly patients is increasing. The aim of this study was to compare laparoscopic cholecystectomy (LC) to antibiotics in elderly patients with acute cholecystitis. Methods: A randomized multicenter clinical trial including patients over 75 years with acute calculous cholecystitis was conducted in four hospitals in Finland between January 2017 and December 2019. Patients were randomized to undergo LC or antibiotic therapy. Due to patient enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…A randomized clinical trial and retrospective cohort study comparing laparoscopic cholecystectomy versus antibiotic therapy for acute cholecystitis in elderly patients found that the length of hospital stay, and complications were lower in the laparoscopic cholecystectomy group. This trial concluded that laparoscopic cholecystectomy showed be offered to elderly patients with acute cholecystitis [38].…”
Section: Timing Of Cholecystectomy In Acute Cholecystitismentioning
confidence: 99%
“…A randomized clinical trial and retrospective cohort study comparing laparoscopic cholecystectomy versus antibiotic therapy for acute cholecystitis in elderly patients found that the length of hospital stay, and complications were lower in the laparoscopic cholecystectomy group. This trial concluded that laparoscopic cholecystectomy showed be offered to elderly patients with acute cholecystitis [38].…”
Section: Timing Of Cholecystectomy In Acute Cholecystitismentioning
confidence: 99%